PENDIDIKAN MULTIKULTURAL DI PERGURUAN TINGGI ISLAM BERBASIS BOARDING SCHOOL INSTITUT AGAMA ISLAM TAZKIA - Nabella Dananier (Institut Agama Islam Ngawi, 2022)
Abctract: The diverse culture of IAI Tazkia students is a separate demand for the campus in implementing a borading school-based education program. The low sense of social sensitivity as a result of the use of gadgets in generation Z (currently at the age of high school and college) makes intolerance more visible among students. This will be a difficult thing for students studying at the IAI Tazkia boarding school. So the campus needs to provide program content or activities that contain the values ​​of multiculturalism. The method in this study uses a qualitative description method with data collection through interviews, observation and documentation. The results of this study indicate that IAI Tazkia, especially in the Tadris Podi that the researchers studied, there are 7 programs that contain multicultural education which includes: courses on multicultural education and community development, SDS or student dynamic sessions, hidden curriculum, the academic community and the campus environment that supports education. multicultural activities in the campus area, student organizations, student appreciation programs, competitions in matriculation programs. Keywords: Multicultural Education, Boarding School, IAI Tazkia